The influence of heavy metallic wastes on the physical properties and gamma-ray shielding performance of ordinary concrete: Experimental evaluations. (May 2023) - Mahmoud, K.G.; Alqahtani, Mohammed S.; Tashlykov, O.L.; Semenishchev, V.S.; Hanfi, M.Y.
Abstract: Four ordinary concrete samples were fabricated at room temperature with well mixing of the concrete components (cement- M400, granite with grain size ≥20 mm, sand, and metallic waste powder). The density of the fabricated concrete was measured using the MH-300 A density meter where it decreased from 2.45 to 2.37 g/cm 3 . The pore and bulk volumes as well as the porosity were measured of the fabricated concrete. Both pore volume and bulk volume show an increase with raising the metallic waste content between 0 and 30 wt%. The narrow beam transmission method with NaI (Tl) detector was utilized to evaluate experimentally the linear attenuation coefficient (μ, cm −1 ) of the fabricated concrete. The experimental measurements were performed using many radioactive isotopes (Ba-133, Na-22, Eu-152, Cs-137, and Co-60) as sources for γ-ray emit photons with energy expanded from 81 keV to 1408 keV. The μ values show an enhancement by a factor of ≈33% with raising the metallic waste content between 0 and 30 wt%, at γ-photon energy of 662 keV. Highlights: Four ordinary concrete doped metallic waste powder were fabricated. Raising the metallic waste powder increases voids inside the fabricated concrete. The fabricated concretes' porosity increased with raising the metallic waste powder. The linear attenuation coefficient enhanced by increasing the metallic waste powder.